Heterogeneity of Lung Phagocytes and Clearance of Apoptotic Cells in Lung Injury and Repair - Bersie, Stephanie M.; McCubbrey, Alexandra L. (Seminars in Respiratory and Critical Care Medicine, 2025)
Poor repair following lung injury is a significant cause of morbidity and mortality. Clearance of apoptotic cells, termed efferocytosis, has emerged as a key process that can influence repair outcomes and facilitate successful repair. Although prior literature has focused on efferocytosis by macrophages, evidence is emerging that nonprofessional phagocytes, including fibroblasts and epithelial cells, may play critical roles in efferocytosis during tissue repair. This review summarizes existing knowledge of different lung phagocytes that can participate in efferocytosis, evidence linking efferocytosis to lung health and tissue repair, and discusses factors that may inhibit or redirect efferocytosis to promote mis-repair. A deeper understanding of how the integrated landscape of lung phagocytes participates in efferocytosis will likely provide significant insight into repair and mis-repair processes.
Keywords: efferocytosis; apoptotic cell clearance; lung; macrophage; nonprofessional phagocyte; repair